Workers' Job Prospects and Young Firm Dynamics - Seula Kim (Institute of Labor Economics (IZA), 2025)
This paper investigates how worker beliefs and job prospects impact the wages and growth of young firms, as well as the aggregate economy. Building a heterogeneous-firm directed search model where workers gradually learn about firm types, I find that learning generates endogenous wage differentials for young firms. High-performing young firms must pay higher wages than equally high-performing old firms, while low-performing young firms offer lower wages than equally low-performing old firms. Reduced uncertainty or labor market frictions lower the wage differentials, thereby enhancing young firm dynamics and aggregate productivity. The results are consistent with U.S. administrative employee-employer matched data.
Keywords: E20; E24; J31; J41; J64; L25; L26; M13; M52; M55; 330; Wage Differentials; Firm Dynamics; Learning; Search Frictions; Uncertainty